First evidence of predation on an adult porbeagle equipped with a pop-off satellite archival tag in the Northwest Atlantic - Anderson, Brooke N.; Horstmyer, Lauren; Ballard, Kirsty L.; Dodd, Jon F.; Sulikowski, James A. (Frontiers in Marine Science, 2024)
Pop-off satellite archival tags (PSATs) have been increasingly deployed on marine megafauna to remotely monitor their movements, behavior, and environmental preferences. These tags have also allowed the occasional novel documentation of ecological interactions, such as predation on tagged animals. A PSAT deployed on a pregnant porbeagle Lamna nasus in the Northwest Atlantic suggests the shark was predated upon in mesopelagic waters near Bermuda. Predation was evident approximately 5 months after tagging based on depth and temperature data transmitted by the PSAT. Four days prior to PSAT pop-off, depth data indicated that the tag continued to descend and ascend in the water column while the temperature remained approximately 5°C above ambient levels, even at several hundred meters in depth, indicating ingestion. Given the location of predation and elevated temperature at depth recorded by the pregnant porbeagle’s tag, potential predators include endothermic shark species such as the white shark Carcharodon carcharias and shortfin mako Isurus oxyrhinchus. This is the first evidence of predation on a porbeagle globally and provides novel insight into inter-specific interactions for this large, threatened shark species.